Prescribing pattern of antibiotics in AL-Elwia Pediatric Teaching Hospital, Baghdad, 2016. - Obaid, Ali Abdul-Razzaq (AL-Kindy College Medical Journal, 2019)
Background: Antibiotics are among the most commonly used medicine, in both community and hospital setting, all over the world especially in countries where no strict guideline to regulate their use. In Iraq, only a few studies conducted to describe the antibiotic prescription pattern in general hospitalsand even less in pediatric hospital.Objective: To describe the patterns for antibiotics used in Elwia pediatric teaching hospital in Baghdad, IraqType of the study: Descriptive cross sectional study..Methodology: The study was conducted at AL-Elwia Pediatric Teaching Hospitalduring the year 2016. A random sample from all the prescriptions sheets, of patients consulting outpatient clinic or admitted to different departments were studied for different parameters in different departments of the hospital.Results:A total number of 9440 prescriptions, were collected and analyzed.The age group 1-5 years was the most common group consulting the hospital followed by those below 6 months of age. About 51% of all patients were males. The study revealedthat 87.56% of all patients consulting the hospital were received antibiotics. The highest rate of antibiotic used was in inpatient department (99.9%) followed by NNCU (92.11%). Amoxicillin was the most preferred antibiotics by pediatrician in outpatient, inpatient and ER department.Conclusion: The results of this study indicate that there is, in general, overuse of antibiotics in all hospital departments when compared with other developing countries.